Carbon dioxide sequestration on fly ash/waste glass alkali-based mortars with recycled aggregates: Compressive strength, hydration products, carbon footprint, and cost analysis - Mastali, Mohammad (2018)
Carbon dioxide sequestration is crucial for limiting global warming. However, carbon dioxide sequestration in saline aquifers has large risks and also involves a very high cost. In this context sequestration of carbon dioxide in cementitious construction materials can not only prevent carbon dioxide to be released into the atmosphere but also accelerate curing and strength development of those materials. Since so far no studies were performed on alkali-based materials, this chapter discloses results of an investigation concerning carbon dioxide sequestration on fly ash/waste glass alkali-based mortars with recycled aggregates. Compressive strength, hydration products, carbon footprint, and cost analysis were also studied.